"Sanggah Kemulan: A Sacred Shrine in Balinese Hinduism for Spiritual Connection with the Divine" - Nuriani, Ni Kadek (Bali Tourism Journal, 2023)
The reverence for Hyang Guru and Tri Murti is an embodiment of the spiritual wealth and local wisdom in the religious practices of the Indonesian community. In the context of Hindu beliefs and culture, pivotal concepts such as Tri Murti and Hyang Guru assume roles of profound significance. Tri Murti encapsulates three divine facets: Brahma as the creator, Vishnu as the preserver, and Shiva as the destroyer. Conversely, Hyang Guru is perceived as a manifestation of divinity, embodied in the form of a teacher or spiritual figure. Sang Hyang Guru, originating from the oldest Hindu scripture, the Vedas, has existed since the creation of the universe. In Bali, Bhatara Guru is revered as an ancestor who underwent sacred ceremonies. Sang Hyang Guru is a central concept in Hinduism, considered the highest deity, creator of the universe, and the source of all knowledge, serving as the ultimate teacher for humanity. Sanggah Kamulan, introduced by Mpu Kuturan, aims to unite sects in Bali under the Tri Murti concept, comprising Brahma, Vishnu, and Shiva. Sanggah Kamulan, a center for worship activities, signifies the transformed Tri Murti as manifestations of worship as meme-bapa raganta jati. Bapanta on the right symbolizes the father of the sky, ibunta on the left as the mother earth, and their union as raganta jati (Shiva) in the middle. The principle of meme-bapa raganta jati inspires its entire doctrine, with Sanggah Kamulan established in Balinese households before the introduction of Hinduism to Indonesia.